Risk‐stratifying clinicopathologic criteria for ovarian preservation in premenopausal women with early stage low‐risk endometrial cancer. Issue 3 (26th June 2020) - Khadraoui, Wafa; Tierney, Christina; Chung, Sophie; Mutlu, Levent; Lu, Lingeng; Azodi, Masoud; Ratner, Elena; Menderes, Gulden
Abstract: Objective: To establish the rate of occult ovarian micro‐metastases in early stage disease and to provide an eligibility framework for providers to consider ovarian preservation in a patient population with presumed early stage disease. Methods: A retrospective review from January 2005 to December 2010 identified women with presumed early stage endometrial cancer from a single institutional database. Inclusion criteria included: (1) FIGO grade 1 endometrioid endometrial cancer on endometrial biopsy; or (2) the same pathology as (1) on frozen section specimen with less than 50% myometrial biopsy; and (3) no evidence of metastatic disease on preoperative imaging or visible metastatic disease in the peritoneal cavity. Results: Of the 52 patients, 86.5% were diagnosed with stage IA and 11.5% were diagnosed with stage II disease. One patient (1.9%) had microscopic adnexal involvement in a fallopian tube, which upstaged her to stage IIA disease. None of the patients had ovarian involvement. Conclusion: Preservation of the ovaries appears to be a safe and viable option for premenopausal women who are diagnosed with presumed early stage endometrioid endometrial cancer. It is believed that ovarian preservation in this select population will provide them with significant health benefits and improve their quality of life. Abstract : The study data support low incidence of microscopic adnexal metastasis in early stage low‐risk endometrial cancer and provides risk‐stratifying clinicopathologic criteria for ovarian preservation.